Combining Sodium Butyrate With Cisplatin Increases the Apoptosis of Gastric Cancer In Vivo and In Vitro via the Mitochondrial Apoptosis Pathway - Li, Yangbo; He, Pengzhan; Liu, Yinghui; Qi, Mingming; Dong, Weiguo (Frontiers in Pharmacology, 2021)
Introduction: Gastric cancer (GC) as one of gastrointestinal malignancies commonly has a high incidence worldwide. Cisplatin (DDP) is a type of traditional chemotherapeutic drugs which is generally applied to anti-cancer, however, drug tolerance remains affecting the efficacy. Sodium butyrate (NaB) as an intestinal flora derivative has been shown to have general anti-cancer effects in vitro and in vivo through pro-apoptosis and improving the prognosis by combining with traditional chemotherapy drugs. Methods: CCK-8 assay was used to assess the proliferation viability of GC cells in vitro. Hoechst 33258 staining and Annexin V-PE/7-AAD were used to qualitatively and quantitatively detect apoptosis in GC cells. Intracellular reactive oxygen species (ROS) measurement and mitochondrial membrane potential (MMP) assay kit were used to qualitatively reflect the function of mitochondria in GC cells. Western blotting was used to verify the above experimental results. Nude mouse with xenograft tumor model was used to value the anti-tumor efficacity of NaB and DDP in vivo. Results: NaB combined with DDP can increase apoptosis in GC cells. In a nude mouse with xenograft tumor model, we observed remarkable that NaB in combination with DDP can inhibit the growth of tumor more effectively than single agent regimens. We obtained the combination of NaB and DDP facilitated the increasing trend of intracellular ROS and the decreasing trend of the MMP, meanwhile, suppressed the invade and migrate abilities in GC cells. We used western blotting to verify that NaB plus DDP significantly enhanced the levels of mitochondrial apoptosis-related pathway proteins expressed. Conclusion: NaB, a histone acetylation inhibitor produced by intestinal flora fermentation, and its combination with DDP enhances the promotion of apoptosis trend of GC cells through the mitochondrial apoptosis-related pathway and we could take into account it as a potential therapeutic option for GC.